Aspects of energetic substrate metabolism of in vitro and in vivo bovine embryos - Souza, Danielle Kaiser de (2015)
Although the metabolism of early bovine embryos has not been fully elucidated, several publications have addressed this important issue to improve culture conditions for cattle reproductive biotechnologies, with the ultimate goal of producing in vitro embryos similar in quality to those developing in vivo. Here, we review general aspects of bovine embryo metabolism in vitro and in vivo, and discuss the use of metabolic analysis of embryos produced in vitro to assess viability and predict a viable pregnancy after transference to the female tract.